Dynamic policy analysis - Jaap H. Abbring; James J. Heckman (Centre for Microdata Methods and Practice (cemmap), 2008)
This chapter studies the microeconometric treatment-effect and structural approaches to dynamic policy evaluation. First, we discuss a reduced-form approach based on a sequential randomization or dynamic matching assumption that is popular in biostatistics. We then discuss two complementary approaches for treatments that are single stopping times and that allow for non- trivial dynamic selection on unobservables. The first builds on continuous-time duration and event-history models. The second extends the discrete-time dynamic discrete-choice literature.
Keywords: 330; Wirkungsanalyse; Mikroökonometrie; Panel; Dynamisches Modell; Statistische Bestandsanalyse; Event Study; Diskrete Entscheidung; Theorie